Changes in Attitudes Toward Anemia Prevention Through Counseling Based on Health Belief Model Theory in Early Adolescent Children at Junior high school Nurul Islam Jember - Aidah, Hasnah; Bachri, Syaiful; Palupi, Jenie (Universitas Bondowoso, 2023)
Background: Based on the results of the anemia control program by the Jember District Health Office in 2018, anemia among adolescents was 41.6%, data from the preliminary study results, most students considered that adolescents were not at risk of anemia and considered that anemia did not affect their academic achievement, how the easiest way to prevent anemia is by taking blood-boosting tablets that have been programmed by the government. One such phenomenon is a negative attitude towards anemia prevention. The purpose of this study was to analyze changes in attitudes towards preventing anemia through counseling based on the HBM (Health Belief Model) theory for adolescents. Methods: The research design used a pre-experimental design with a one-group pretest-posttest study design. The number of respondents in this study were 152 female students who were taken based on inclusion and exclusion criteria by means of stratified random sampling from class VII-IX Junior high school Nurul Islam Jember. Results: With the Mc Nemar test, the results obtained α value <0.05, namely 0.000, it can be concluded that there is a change in attitude before and after being given counseling about preventing anemia in early adolescents at Junior high school Nurul Islam Jember. Conclusion: Health education about anemia prevention with interesting material and media as well as the HBM (Health Belief Model) method is proven to be able to improve adolescent attitudes because it emphasizes one's belief that young women are very at risk of developing anemia and has an impact on decreased school achievement and disrupted growth. This treatment needs to be done repeatedly in order to give a deep impression.